Collateral damage: toxic effects of targeted antiangiogenic therapies in ovarian cancer - Stone, Rebecca L (2010)
First-line chemotherapy fails in more than 20% of patients with epithelial ovarian cancer and about 40–50% of women who respond to initial treatment relapse within 2 years. In the recurrent setting, second-line chemotherapeutic agents have a 15–20% response rate with no cures. Fortunately, clinical investigations that have assessed the efficacy of new, biologically targeted therapies have reinvigorated therapeutic options for patients living with ovarian and other malignancies. In view of the fact that ovarian cancer is one of the most angiogenic neoplasms, there is great hope that implementing targeted agents with antiangiogenic properties will improve outcomes. However, as experience grows with the antitumour activity of these drugs, new toxic effects are emerging. The effects of antiangiogenic agents on molecules and processes that also have physiologically important roles in healthy tissues are at the crux of these toxic effects, or “collateral damage”. This review discusses the leading toxic effects encountered and anticipated in clinical investigation and practice with antiangiogenic agents in patients with ovarian cancer, with particular focus on potential management strategies.